Effects of Fiberglass on the Strength of Reclaimed Asphalt Pavement (RAP) as a Subbase Materials - Mostafa, Ahmed Mahmoud A.; M. Morsi, Ahmed Gamal; E. Hegazy, Alnos Aly (International Journal of Advanced Engineering, Management and Science, 2023)
This research study investigates the effect of fiberglass content on the strength of Reclaimed Asphalt Pavement (RAP) material as a subbase layer of flexible pavement. Laboratory modified proctor and California bearing ratio (CBR) tests were conducted on the mixture of RAP and fiberglass. The obtained results show that, 100% RAP material can be used as subbase material. In addition to that, there is a slight reduction in maximum dry density (γdmax) values when RAP is blended with fiberglass. Similarly, the soaked and unsoaked CBR values of the mixture decreased slightly. However, the mixture of RAP and fiberglass achieved the specification requirements as a subbase layer according to the Egyptian specifications. The relationship between fiberglass content and maximum dry density of RAP is found to be linear. Also, a linear relationship exists between percentage of fiberglass and unsoaked CBR. Finally, the relationship between the percentage of fiberglass and soaked CBR is found to be nonlinear.